MDCT arthrography assessment of the severity of cartilage damage and scapholunate dissociation in regard to specific-component tears of the scapholunate interosseous ligament. Issue 125 (April 2020) - Quere, Jean-Baptiste; Phan, Catherine; Miquel, Anne; Li, Ling; Arrivé, Lionel; Menu, Yves; Crema, Michel D.
Highlights: Complete tears of the dorsal component of the scapholunate ligament are the most pejorative. Greater severity of scapholunate dissociation is associated with SLAC wrist. A cut-point scapholunate dissociation value of 3.7 mm may be useful to predict SLAC. Abstract: Purpose: To evaluate the distribution and severity of cartilage damage and scapholunate dissociation assessed on multi-detector computer tomography (MDCT) arthrography in a sample of patients with scapholunate interosseous ligament (SLIL) injury, in regard to component-specific tears. Methods: We retrospectively included 37 patients with SLIL tears and 34 patients without SLIL tears who served as controls, all patients had undergone MDCT arthrography. Morphology of SLIL dorsal and volar components was graded as: normal, partial, or complete tear. Cartilage damage was assessed in 14 distinct regions of the wrist using a semiquantitative modified scoring system. Staging of scapholunate advanced collapse (SLAC) for each patient was based on the distribution of cartilage damage seen on MDCT arthrography. Scapholunate dissociation was measured for each patient at the tenth of a millimeter. The Student's t -test (p) and the Wilcoxon Rank-Sum test (P) were used to compare the different groups. Results: The cartilage damage scores obtained were greater in patients with complete SLIL dorsal component tear than in other patients (p = 0.0019 and P = 0.0018). Scapholunate dissociation was greater in these patients (p = 0.0003 and P = 0.0013). Scapholunate dissociation was also greater in patients with SLAC wrist (p = 0.0004 and P = 0.0012), with a cut-off value of 3.7 mm for diagnosing SLAC (sensitivity 83.3 % and specificity 89.5 %). Conclusion: MDCT arthrography assessment shows that the severity of cartilage damage and scapholunate dissociation is greater when the dorsal component of the SLIL is completely ruptured.